Correlation Between History of ISTC Training on Independent Practicing Doctor With Discovery of TB Suspected Children in Surabaya City - Madu Puspita Nuansa Jatu; Fariani Syahrul (Humanistic Network for Science and Technology (HNST), 2018)
The burden of Tuberculosis in children cases in the world is unknown due to the lack of diagnostic tools that are